Peningkatan Kapasitas UMKM Wingko Riona Berkelanjutan Berbasis Kemitraan Perguruan Tinggi - Winanto Nawarcono; Luluk Kholisoh; Sapta Aji Sri Margiutomo; Eliya Isfaatun; Maria Magdalena PD (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The COVID 19 pandemic has had an impact on food MSMEs by Wingko Riona. Production decreased drastically from 3,000/day with a workforce requirement of 7 people, decreasing to only being able to produce 900/day with a workforce of 1 person. This decline has the effect of decreasing MSME income. University partnership-based MSME assistance aims to increase the capacity of MSMEs so that they can be sustainable. The program carried out is to increase production, namely with a product innovation training program and innovation in cooking methods other than using an oven, namely using iron frying pan equipment. The financial literacy training program was carried out to provide MSMEs with an understanding of the importance of keeping financial records and knowing the production costs required for each wingko production. The method used is lecture training and direct practice accompanied by experts and a team of lecturers and students at STIE Nusa Megarkencana. MSMEs are able to innovate wingko products with Durian, Jackfruit and Banana flavors. MSMEs know of a new way of producing wingko using equipment other than an oven, which turns out to provide better results and is easier. In Financial Literacy, MSMEs can find out how to calculate production costs correctly so they can determine production cost requirements and profits obtained at the set wingko prices. MSMEs can also understand the importance of creating cash flow and financial reports.